Value of Improved Information about Forest Protection Values, with Application to Rainforest Valuation - Strand, Jon (World Bank, Washington, DC, 2015)
What is the utility from obtaining more precise values of natural resource objects (rainforests), through surveys or other similar information gathering? In the value of information problems studied here, a principal who wishes to preserve a resource sets a price to offer to a seller without knowing precisely the protection value or opportunity value, to the seller. The value of information related to more precise information about the protection value for the principal is a key issue in environmental and natural resource valuation, but it is in most cases implicit and not analyzed. More precise resource values reduce the frequency of two types of mistakes (saving the resource when it should not be saved, and not saving the resource when it should be saved), and increases the principal’s ex ante expected utility value. This paper applies the model to Amazon rainforest protection and considers the hypothetical value of perfect information. The analysis finds that the value of perfect information can easily exceed realistic information costs, thus perhaps justifying significant expenditures for valuation studies, given that all available information is used efficiently for conservation decision purposes. The value of perfect information also depends on the nature of buyer-seller interactions, and is higher in the altruistic case, where the principal has full concern for the outcome for the seller.